Lost in the Weeds?: A Comprehensive Guide to Florida’s Many Non-Native Plant Lists - Deah Lieurance; Lyn A Gettys (EDIS, 2019)
Because researchers and land managers in Florida have been dealing with invasive species for decades, there is an abundance of resources available to the public regarding invasive species. Sometimes, the volume of available information can be confusing. This 6-page document aims to inform the general public, land managers, researchers, local and state policy makers, and others who seek guidance in accessing regulatory and nonregulatory non-native plant lists in the state of Florida. This publication explains the origins of the lists, meaning of inclusion on a particular list, and ways to access each of the lists. Written by Deah Lieurance and Lyn A. Gettys, and published by the UF/IFAS Agronomy Department, August 2019. http://edis.ifas.ufl.edu/ag436